Art et histoire : l’excès dans Demos de George Gissing - Christine Huguet (Cahiers Victoriens et Edouardiens)
The artist in quest for adequate modes of representation of excess not infrequently turns his hand to the historical novel, a genre overtly legitimising the imagination. But he cannot overlook the fact that addressing a specific past and calling upon collective memory also render his task as an illusionist far more complicated. In Demos George Gissing meets the challenge and evinces keen awareness of the necessity both to accommodate the possibilities suggested by his material and to avoid being constrained by it, hence the deconstructive subtitle, « A Story of English Socialism », a clear warning of imaginative departure from mere factuality. This article examines Gissing’s metahistorical enquiry with a view to defining how far pliant historiographic de/reconstruction of unrest and agitation may facilitate the integration of the artist’s own excessive responses.